2010
DOI: 10.1111/j.1471-0307.2010.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on the antibacterial activity of bovine lactoferrin against three foodborne pathogens

Abstract: The effect of different heat treatments on the antimicrobial activity of bovine lactoferrin against Escherichia coli O157:H7, Salmonella enteritidis and Listeria monocytogenes has been studied. We have observed that the heat treatments lower than 85°C for 10 min did not affect the antibacterial activity of the protein. Hydrolysates of bovine lactoferrin were found to be more active than the native protein against the three pathogens. Moreover, the antibacterial effect of bovine lactoferrin was also assayed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 28 publications
5
16
0
Order By: Relevance
“…As shown in Table , LTLT, HTST, and UHT pasteurization enabled the preservation of 50, 80, and 15% of milk LF, respectively. Our results are in agreement with previous studies (Abe et al, ; Conesa et al, ; Peila et al, ; Sánchez et al, ), which reported similar rates of preservation of LF for milks subjected to HTST (≥90%) and UHT (≤10%) treatments. As observed for IgG, microwave treatments with lower temperature (treatments 1 and 9) favored the preservation of LF (30%–50%).…”
Section: Resultssupporting
confidence: 94%
“…As shown in Table , LTLT, HTST, and UHT pasteurization enabled the preservation of 50, 80, and 15% of milk LF, respectively. Our results are in agreement with previous studies (Abe et al, ; Conesa et al, ; Peila et al, ; Sánchez et al, ), which reported similar rates of preservation of LF for milks subjected to HTST (≥90%) and UHT (≤10%) treatments. As observed for IgG, microwave treatments with lower temperature (treatments 1 and 9) favored the preservation of LF (30%–50%).…”
Section: Resultssupporting
confidence: 94%
“…Initially, all the samples containing only albumin (OVA 3% w/v) were adjusted to pH 8.0; the samples containing only lactoferrin (Lf 3% w/v) were adjusted to pH 7.0; and all the emulsions containing the protein mixtures were adjusted to pH 6.0, being the pH at which the emulsions showed higher stability at 25 °C. Emulsions containing 3% w/v Lf showed larger-diameter droplets, indicating an initiation of aggregation close to 60 °C, which is indicated as the first denaturation temperature of Lf [24] . Figure 3-I shows the droplet diameter of emulsions containing 3% w/v Lf (pH 7.0), 3% w/v OVA (pH 8.0) and mixtures with different proportions Lf:OVA and a pH between the isoelectric points of the proteins (6.0).…”
Section: Influence Of Temperaturementioning
confidence: 97%
“…In particular, the ability of bovine lactoferrin to regulate bone cell growth has been well established (Cornish et al, 2004) and furthermore, oral feeding trials in ovariectomised rats (Blais, Malet, Mikogami, Martin-Rouas, & Tomé, 2009;Guo et al, 2009) and healthy postmenopausal women (Bharadwaj, Naidu, Betageri, Prasadarao, & Naidu, 2009) have indicated the potential of this bioactive protein in ameliorating bone loss during menopause. Although lactoferrin occurs naturally in milk, levels in bovine milk are relatively low (Cheng et al, 2008;Indyk & Filonzi, 2005) and the heat treatments required during manufacture and processing of dairy products are likely to cause denaturation of the protein and loss of bioactivity (Conesa et al, 2010;Schwarcz, Carnelocci, Silva, Oliveira, & Goncalves, 2008). Hence supplementation with commercially isolated non-denatured lactoferrin is an effective way to supply this bioactive ingredient.…”
Section: Introductionmentioning
confidence: 98%
“…As lactoferrin is a heat-sensitive protein and high temperatures such as those employed to pasteurise the yoghurt mix prior to fermentation are likely to result in the loss of bioactivity (Conesa et al, 2010;Schwarcz et al, 2008), it must be added either with the starter culture or following fermentation to avoid heat denaturation and loss of functionality. Although lactoferrin is a protein with broad spectrum antimicrobial properties (Jenssen & Hancock, 2009), studies have shown that it can act as a growth factor for certain probiotic Bifidobacterium strains (Rahman, Kim, Kumara, & Shimazaki, 2010) and additionally, it does not appear to have any growth inhibition activity against a variety of Lactobacillus strains (Tian, Maddox, Ferguson, & Shu, 2010).…”
Section: Introductionmentioning
confidence: 99%